Does decentralized governance lead to less scientific output? - Zupan, Blaž (Lex localis, 2017)
This paper argues that national innovation infrastructure is closely linked with the scientific output and that some other factors, such as decentralized governance, can in certain combinations with innovation infrastructure lead to a higher scientific output. It demonstrates this by using a set-theoretic fsQCA method to analyze the data on national innovation capacities, fiscal decentralization, and science policy output. Results confirm that while a national innovation infrastructure is a necessary condition for successful scientific output, decentralization in certain, but not all cases leads to successful scientific output and that the paths to a successful scientific output in different countries are diverse.
Keywords: fiskalna decentralizacija; inovacije; inovacijska politika